The Early Education Teacher`s Workshop and Professional Awareness - Jolanta Kruk (University of Lower Silesia, 2015)
This article reflects the issues of an early education teacher`s workshop as significant but underestimated component of professional awareness. It presents the Lab of Early Education as the exemplar of work, where the teachers collaborate with students and can reach professional awareness and pedagogic autonomy.